KUALITAS KARKAS DAN ANALISIS EKONOMI AYAM BROILER YANG DIBERI DUA JENIS KONSENTRAT KOMERSIAL - Vinka Adhi Pratika; Sri Sukaryani (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
ABSTRACTThe increasing demand for chicken meat requires strategic efforts to improve the carcass quality of broiler chickens. One approach to achieve this objective is through effective feed management. This study aimed to evaluate the effects of feeding two different commercial concentrates on carcass quality (carcass percentage and abdominal fat) and economic efficiency (feed cost per gain) of broiler chickens. The experiment was conducted using a Completely Randomized Design (CRD) and analyzed by analysis of variance (ANOVA), consisting of three dietary treatments with four replications, each replication containing three broiler chickens. The treatments included P1: broilers fed 100% commercial concentrate A; P2: broilers fed 100% commercial concentrate B; and P3: broilers fed a mixture of 50% commercial concentrate A and 50% commercial concentrate B. The optimal results were observed in P1, with a carcass percentage of 73.92%, abdominal fat percentage of 1.05%, and feed cost per weight gain of IDR 13,790. In contrast, the lowest results were recorded in P3 (50% commercial concentrate A and 50% commercial concentrate B), with a carcass percentage of 70.87%, abdominal fat percentage of 1.16%, and feed cost per weight gain of IDR 13,873. It can be concluded that the use of different commercial concentrates significantly affected carcass quality, particularly carcass percentage, but had no significant effect on abdominal fat percentage or feed cost per gain in broiler chickens.Keywords: abdominal fat, broiler chicken, feed cost per gain, carcass, commercial feed